Factors affecting length of stay in Fournier’s gangrene: a retrospective analysis of 10 years’ data - Eksi, Mithat; Arikan, Yusuf; Simsek, Abdulmuttalip; Ozdemir, Osman; Karadag, Serdar; Gurbuz, Necati; Sahin, Selcuk; Tasci, Ali Ihsan (Aktuelle Urologie, 2020)
Background We aimed to investigate the parameters that have an effect on the length of stay and mortality rates of patients with Fournier’s gangrene.Material and Methods A retrospective review was performed on 80 patients who presented to the emergency department and underwent emergency debridement with the diagnosis of Fournier’s gangrene between 2008 and 2017. The demographic and clinical characteristics, length of stay, Fournier’s Gangrene Severity Index score, cystostomy and colostomy requirement, additional treatment for wound healing and the mortality rates of the patients were evaluated.Results Of the 80 patients included in the study, 65 (81.2 %) were male and 15 (18.7 %) female. The most common comorbidity was diabetes mellitus. The mean time between onset of complaints and admission to hospital was 4.6 ± 2.5 days. As a result of the statistical analyses, it was found that Fournier’s Gangrene Severity Index score, hyperbaric oxygen therapy, negative pressure wound therapy and the presence of sepsis and colostomy were significantly positively correlated with length of stay. Also it was found that the Fournier’s Gangrene Severity Index score, administration of negative pressure wound therapy and the presence of sepsis were correlated with mortality.Conclusion Fournier’s gangrene is a mortal disease and an emergency condition. With the improvements in Fournier’s gangrene disease management, mortality rates are decreasing, but long-term hospital stay has become a new problem. Knowing the values predicting length of stay and mortality rates can allow for patient-based treatment and may be useful in treatment choice.
Keywords: Fournier's gangrene; mortality; risk factors; length of stay